STRATEGY TO IMPROVE THE QUALITY OF HUMAN RESOURCES TO ACHIEVE GOOD GOVERNANCE (Case study at the Department of Small and Medium Enterprises cooperative Bantul Regency) - Nursani Budiarti; Suswanta Suswanta (DIA: Jurnal Administrasi Publik, 2020)
The reform of public management will have an impact on the demands of qualifications and competency of human resources in government institutions. Grand Design bureaucracy reform is increasing the capacity and accountability of bureaucratic performance.  Human resources development of government apparatus in the present must be placed and directed at a position that corresponds to the field of duty. This research aims to see the strategy used by the Department of Small and Industrial enterprises of Bantul District to improve the quality of government apparatus to achieve good governance to be achieved a better organizational system. Methods used are qualitative descriptive, the technique of collecting data sources obtained by documentation.